Drug Utilization Evaluation of Pantoprazole in Inpatients of Tertiary Care Hospital - Bollavaram, Charitha; Bhukya, Karteeka; Komuravelli, Shravani; Valupadas, Chandrashekar; Bandaru, Sharvana Bhava; Eggadi, Venkateshwarlu (Journal of Pharmacy Practice and Community Medicine)
Objectives: To review Pantoprazole drug use, prescribing patterns and promote appropriate pantoprazole use. Methods: The study is prospective and observational conducted in inpatients of a tertiary care teaching hospital [MGM hospital]. A total of 1012 cases were enrolled according to our plan of work i.e., inpatients who were under pantoprazole therapy were enrolled in two phases, phase-I (before intervention) and phase-II (after intervention) as we assessed inappropriate use of drug, intervention was developed and implemented and therefore pertinent use of drug is increased. Results: Inappropriate use of drug was found in phase-I and appropriateness in terms of rational use for indication, dose, dosing interval was improved in phase-II, this may be due to implementation of intervention. Conclusion: Rational use of pantoprazole in accordance with appropriate drug for indication, appropriate dose, dosing interval, duration of therapy for specific indication and particular individual was found to be low in phase-I and rational use was improved after intervention in phase-II by implementing criteria and standards rational drug therapy can be achieved. Rational use of pantoprazole should be increased.
Keywords: Drug Utilization Evaluation; Pantoprazole; Proton pump inhibitors; Intervention; Indication; Rational use; Criteria and Standards.